The Broken Lens: How Anti-Fat Bias in Psychotherapy is Harming Our Clients and What To Do About It. Issue 1 (3rd April 2019) - Kinavey, Hilary; Cool, Carmen
Abstract: Anti-fat bias is a persistent and widespread barrier to body liberation that psychotherapists are ethically bound to do something about. Though academics and clinicians have written about the implications of weight stigma in psychotherapy, the prevalence of anti-fat bias in our profession remains and often goes unexamined. Here we explore the nature of anti-fat bias and reasons to shift to a weight-inclusive stance. We offer examples of how anti-fat bias operates in the therapy room and the harm it causes. Anti-fat bias and body-based oppression as forms of microaggressions are explored, and we make the case for body liberation as a social justice issue. We conclude with recommendations for addressing anti-fat bias, including: developing a liberatory consciousness, the importance of moving from awareness to action, examining our relationship to diet culture, ways to avoid stigmatizing language, bringing a social justice lens into the room, and doing our own work so that we stop locating the problem in people's bodies and provide truly bias-free psychotherapy.